Evaluation and prospect of scientific research capacity ranking for community healthcare centres in China - Qian Liu; Jianwei Shi; Dehua Yu; Hua Jin; Xuhua Ge; Hanzhi Zhang; Zhaoxin Wang (Family Medicine and Community Health)
The National Health and Family Planning Commission of the People's Republic of China has proposed to improve the medical capacity of general practitioners and the establishment of general practice in recent health reform. For the first time, the ability to conduct scientific research was included in this reform, which demands community healthcare centres (CHCs) to strengthen their research capacity. The evaluation of community scientific research capacity has become an important endeavour to promote the implementation of research in CHCs. Since 2016, our research team has been working on an evaluation system and has published the scientific research capacity ranking for the top 100 CHCs in China. The latest released ranking of scientific research capacities of China CHCs has aroused great attention in the country.